KEDUDUKAN AKAL DALAM SOSIOLOGI ISLAM: PERDEBATAN ANTARA MAZHAB RASIONAL DAN TRADISIONAL ISLAM - Rifan Shohibul Wafa; Beni Ahmad Saebani (Cahaya Ilmu Bangsa, 2024)
Abstract The position of reason in Islam is a theme that has sparked long debate among Muslim scholars and thinkers. This debate mainly occurs between two main schools of thought: the rational school of thought which prioritizes the use of reason and logic in understanding Islamic teachings, and the traditional school of thought which places more emphasis on revealed texts and religious authority. The rational school, pioneered by figures such as Al-Farabi and Ibn Rushd, argued that reason is the main tool for achieving truth and understanding the essence of religion. They believe that reason can help bridge understanding between revelation and rational reality, resulting in more contextual and relevant interpretations. In contrast, the traditional school of thought, represented by conservative ulama, emphasizes that reason has limits and cannot replace sacred texts. They argue that adhering to revelation is the only way to maintain the sanctity of Islamic teachings and avoid distorted interpretations. This debate not only influences theological understanding, but also has an impact on various aspects of social, political and cultural life in Muslim society. In the current global context, where rational thinking increasingly dominates, it is important for Muslims to re-evaluate the position of reason within the framework of Islamic teachings, by looking for a meeting point between rationality and tradition. This article aims to explore the dynamics of this debate and its implications for contemporary Islamic thought and practice. Abstrak Kedudukan akal dalam Islam merupakan tema yang telah memicu perdebatan panjang di kalangan ulama dan pemikir Muslim. Perdebatan ini terutama terjadi antara dua mazhab utama: mazhab rasional yang mengedepankan penggunaan akal dan logika dalam memahami ajaran Islam, dan mazhab tradisional yang lebih menekankan pada teks-teks wahyu dan otoritas agama. Mazhab rasional, yang dipelopori oleh tokohtokoh seperti Al-Farabi dan Ibn Rushd, berargumen bahwa akal adalah alat utama untuk mencapai kebenaran dan memahami esensi agama. Mereka percaya bahwa akal dapat membantu menjembatani pemahaman antara wahyu dan realitas rasional, sehingga menghasilkan interpretasi yang lebih kontekstual dan relevan. Sebaliknya, mazhab tradisional, yang diwakili oleh kalangan ulama konservatif, menekankan bahwa akal memiliki batasan dan tidak dapat menggantikan teks suci. Mereka berpendapat bahwa berpegang pada wahyu adalah satu-satunya cara untuk menjaga kesucian ajaran Islam dan menghindari penafsiran yang menyimpang. Perdebatan ini tidak hanya berpengaruh pada pemahaman teologis, tetapi juga berdampak pada berbagai aspek kehidupan sosial, politik, dan budaya dalam masyarakat Muslim. Dalam konteks global saat ini, di mana pemikiran rasional semakin mendominasi, penting bagi umat Islam untuk mengevaluasi kembali kedudukan akal dalam kerangka ajaran Islam, dengan mencari titik temu antara rasionalitas dan tradisi. Artikel ini bertujuan untuk mengeksplorasi dinamika perdebatan ini serta implikasinya terhadap pemikiran dan praktik Islam kontemporer.